Boundaryless career drivers – exploring macro-contextual factors in location decisions. Issue 1 (3rd June 2014) - Dickmann, Michael; Cerdin, Jean-Luc
Abstract : Purpose: – The purpose of this paper is to explore what attracts individuals to live in a South East Asian city. It uses a boundaryless career approach that is interested in how people cross-traditional career boundaries, including those related to country and location barriers. Going beyond an individual and organizational view, a more extensive model of location decisions is developed that incorporates broad macro-factor career drivers. Design/methodology/approach: – A large-scale qualitative study explored individual, organizational, political, economic, socio-cultural, technological, ecological, legal, natural and general drivers to live in the city. The authors interviewed 43 individuals who had moved to the city from abroad, were born in the city and still lived there or who were born in the city but had moved to another foreign city. Findings: – Many macro-contextual factors – i.e. day-to-day regulatory stability and transparency, economic growth, friendliness and meritocracy, safety and a good, clean environment – were seen as attractive by all three groups. People who had left the city raised some specific criticism regarding the vibrancy, freedom and creativity of thought. Research limitations/implications: – The study focused on highly skilled individuals who most often had experience in living in different cities to get more reflective views. However, this restricted the generalizability. The findings nuance the understanding of boundaryless careers. Practical implications: – The research expands the normally used attraction factors and develops a broader framework of city attractiveness drivers. The emerging picture can be used by the city administration to manage its global attractiveness while increasing non-regulatory "stickiness" to retain talent. Social implications: – The research has social implications with respect to cross-border boundaryless careers and talent acquisition, management and retention strategies. Originality/value: – The research expands the macro-contextual discussion and goes beyond the dominant focus on individuals and organizations when investigating boundaryless careers. The study uses an innovative method as it does not only interview foreign expatriates but also two further, more neglected groups: local citizens and individuals who had left the city. It develops an extended model of boundaryless location drivers and develops some exemplary propositions.